Multifunctional and asymmetrically superwettable Janus membrane for all-day freshwater harvesting. Issue 4 (14th February 2023) - Song, Minjie; Zhu, Zhigao; Qi, Junwen; Zhou, Yujun; Li, Jiansheng
Abstract : An asymmetrically superwettable Janus membrane utilizes natural resources without CO2 emission for all-day freshwater harvesting. Abstract : Taking advantage of natural resources for freshwater production is the key to alleviating crises during maritime emergencies. Herein, we designed an asymmetrically superwettable Janus membrane for all-day freshwater harvesting; use of this membrane provided a high-quality freshwater supply with excellent solar desalination of 1.55 kg m −2 h −1 (daytime) and fog collection of 11.31 kg m −2 h −1 (nighttime).